Effects of tower-top acceleration feedback control on the dynamic response of support structures of a 15 MW monopile-type wind turbine - Lai, Yongqing; He, Ben; Ding, Jieyi; Lyu, Na; Yang, Yang (Frontiers in Energy Research, 2025)
As the size and installed capacity of the wind turbines continue to evolve globally, the aerodynamics and fatigue damage on the support structures are experienced a corresponding increasing trend. Consequently, the significance of improving the structural safety of the wind turbines has become incredibly critical. To address aforementioned challenges, the tower-top acceleration feedback control technique has emerged as a promising solution to improve stability and long-term operational reliability by mitigating vibrations, reducing fatigue damage, and enhancing overall structural safety. This study aims to comprehensively investigate the influence of tower-top acceleration feedback control on the operational characteristics and structural responses of the IEA 15 MW wind turbine under complex environmental loadings. The key performance indicators involving the responses of the tower and pile foundation have been systematically analyzed with various damping gain parameters. In addition, the fatigue damage analysis has been conducted under 4 m/s to 25 m/s wind speed conditions. The obtained results demonstrate that the tower-top acceleration gain control can significantly reduce the tower-top displacement, acceleration, and pile foundation loads under wind speeds ranging from 6 m/s to 11 m/s and some of severe conditions. Notably, the most significant reduction in maximum, average and standard deviation of the mudline bending moment of the wind turbine is exhibited by as much as 15.27%, 0.83%, and 24.46%, respectively, under a 6 m/s wind speed scenario. However, the demand for gain control is relatively minimal, where the wind turbine reaches its rated rotor speed with the most intense aerodynamics. A similar trend can be found in the fatigue damage at the tower-base, pile-top, sea water level (SWL), and mudline of the support structure of the wind turbine. It can be significantly mitigated due to appropriate gain control under mild and severe environmental scenarios. These findings prove that well-implemented tower-top acceleration feedback control system not only improves the aerodynamic performance of the monopile-type wind turbine, but also enhances the structural safety, thereby providing a reliable technical support for the continuous development of the large-capacity offshore wind turbines (OWTs).